Stages of E-Ticketing Public Service Policy at the North Musi Rawas Police Department - Austin, Trecy; Pangestu, Aji; Masruroh, Ina (Pencerah, 2025)
This research aims to analyze the e-ticketing policy cycle implemented by the North Musi Rawas Resort Police. From planning, drafting, and approval to the implementation of electronic public services. Exploring the supporting and hindering factors in the implementation of electronic public service policies within the North Musi Rawas Police Department. Providing strategic recommendations for optimizing policies and implementation stages of electronic public services in the future. This research is motivated by various problems encountered in the implementation of e-ticketing. Using the policy cycle theory of Hupe and Hill and qualitative methods, data was collected thru interviews, observations, and documentation. The research results show that there are still people who have a poor understanding of the e-ticketing policy, namely the Suku Anak Dalam community. This presents a unique challenge for the North Musi Rawas Resort Police. The researchers also found that although e-ticketing improves traffic efficiency and compliance, there are technical constraints such as internet signal disruptions and manual administrative procedures that need to be addressed. And there are obstacles. This application makes it easier to identify violations and deters offenders, but technology and administrative integration must be improved to optimize its benefits.